Economics of an Islamic economy - Azhar, Rauf A. (Themes in Islamic Studies, 2010)
This book challenges the interventionist stance of Islamic economics as well as its presumption that riba equals interest. An Islamic economy, it argues, is essentially a market economy, but it differs from capitalist economies because both its institutions and the structure of, for example, property rights are specifically Islamic, deriving from Qurʾān and other sources of Islamic law. The book also focuses on the similarities and differences between riba and interest, establishes the often neglected connection between the two, and explores the ramifications of this connection for Islamic financial systems.